2016
DOI: 10.1093/annonc/mdv624
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of everolimus (RAD001), an mTOR inhibitor plus CHOP for newly diagnosed peripheral T-cell lymphomas

Abstract: The everolimus plus CHOP was effective for PTCL patients, and its efficacy might be related with the preservation of PTEN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…In a randomized phase II study to compare the effects of monotherapy with vinorelbine, which disrupts microtubules, versus combined vinorelbine and everolimus for second-line chemotherapy in advanced HER2-negative breast cancer, the combined therapy was not superior to the monotherapy, although the treatment was well tolerated [270]. In a phase II study of everolimus in combination with CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) as a first-line treatment for patients with peripheral T-cell lymphoma, the treatment was efficacious [271]. Immunohistochemistry revealed maintenance of PTEN expression among patients displaying a complete response.…”
Section: Combining Mtor Inhibition With Conventional Chemotherapies Amentioning
confidence: 99%
“…In a randomized phase II study to compare the effects of monotherapy with vinorelbine, which disrupts microtubules, versus combined vinorelbine and everolimus for second-line chemotherapy in advanced HER2-negative breast cancer, the combined therapy was not superior to the monotherapy, although the treatment was well tolerated [270]. In a phase II study of everolimus in combination with CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) as a first-line treatment for patients with peripheral T-cell lymphoma, the treatment was efficacious [271]. Immunohistochemistry revealed maintenance of PTEN expression among patients displaying a complete response.…”
Section: Combining Mtor Inhibition With Conventional Chemotherapies Amentioning
confidence: 99%
“…The ORR was 90% with CR in 17 patients and PR in 10 patients. Interestingly, the efficacy was associated with loss of PTEN [65]. We investigated the salvage chemotherapy using gemcitabine, dexamethasone, and cisplatin (GDP) for patients with relapsed or refractory PTCL (CISL 1003).…”
Section: Ptcl and Other Subtypes Of T-cell Neoplasmsmentioning
confidence: 99%
“…Recently a phase I/II study on everolimus and alemtuzumab has been published but the authors concluded that results were not sufficiently efficacious (33% PR, no CR) to recommend further development of this regimen (Zent et al, 2016). Immunohistochemistry was used to evaluate the expression of PTEN and pS6K as a marker of response and the difference in CR rate among different subtypes was probably linked to PTEN loss (Kim et al, 2016). Thirty patients received everolimus for six cycles or until dose-limiting toxicity or progression.…”
Section: Lymphomasmentioning
confidence: 99%
“…Positive results (90% objective response) have also been shown in T-cell lymphoma when everolimus (5 mg/day from day 1-14) was combined with CHOP (cyclophosphamide, doxorubicin, vincristine, prednisolone). Immunohistochemistry was used to evaluate the expression of PTEN and pS6K as a marker of response and the difference in CR rate among different subtypes was probably linked to PTEN loss (Kim et al, 2016). Adding temsirolimus to rituximab in a phase II study in Rel/Ref MCL patients produced an ORR of 59%, with 19% CR .…”
Section: Lymphomasmentioning
confidence: 99%